APULEIUS AND THE CODEX REGINENSIS - Stover, Justin Anthony (Exemplaria Classica, 2015)
This article explores the place of Bibliotheca Apostolica Vaticana, Reginensis latinus 1572 in the manuscript tradition of Apuleius’ philosophica. I show that its text is independent of those of the two major families, ? and ?, and that it represents a third branch of the stemma.